2016
DOI: 10.3389/fnagi.2016.00144
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of Pain in the Older Population: The Place of Opioids

Abstract: Pain is a common symptom in older people. It is possible that pain is underreported in older persons due to an incorrect belief that it is an inevitable part of aging. Opioid analgesics are potent medications, with confirmed efficacy for the treatment of moderate to severe pain. These drugs are commonly used in older persons. However, there is insufficient evidence regarding safety of opioids in older patients. One of the reasons for this is the lack of randomized, controlled clinical trials. People of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
(58 reference statements)
0
31
1
2
Order By: Relevance
“…Older age, for example, has been identified as a predictor of opioid treatment response in some studies 47–49 but not in others 21,22,49 . These conflicting findings could result from the mixed changes that occur with ageing, such as increased pain sensitivity, higher level of opioid active metabolites in plasma, and decreases in µ‐opioid receptor densities accompanied by an increase in affinity 50–52 . In addition, a history of alcohol or drug problems has been shown to influence treatment response 53 or pain/opioid tolerance, 54–56 which could result in decreased efficacy of pain treatment as reported in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Older age, for example, has been identified as a predictor of opioid treatment response in some studies 47–49 but not in others 21,22,49 . These conflicting findings could result from the mixed changes that occur with ageing, such as increased pain sensitivity, higher level of opioid active metabolites in plasma, and decreases in µ‐opioid receptor densities accompanied by an increase in affinity 50–52 . In addition, a history of alcohol or drug problems has been shown to influence treatment response 53 or pain/opioid tolerance, 54–56 which could result in decreased efficacy of pain treatment as reported in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…The opioid pathway is typically involved in the analgesic effects of various medications [44][45][46] and in fact opioids are the most common medical therapies for pain. It had been reported that the sympathetic nervous system could be inhibited by opioid peptides produced in the heart through the respective receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are used to manage moderate to severe pain (11) and can be used with older adults when they have pain despite other treatments (2,12). Short-term opioid use has some benefit in older adults with chronic non-cancer pain (13,14).…”
Section: Introductionmentioning
confidence: 99%